Design and Construction of Overcurrent Soft Starting on ESP32 Microcontroller Based Water Machine - Situmorang, Deslan; Paramitha, Nina (Universitas Nusa Putra, 2024)
The advancement of household water pump technology utilizing induction motors provides numerous benefits, such as efficiency and low cost, but also faces challenges like high inrush current. This study demonstrates the necessity of voltage reduction methods to address high inrush currents that can impact home electrical systems. Testing reveals that the device's error percentage is 0.31%, indicating good performance. The DHT22 and PZEM sensors operate optimally in detecting temperature and current, and controlling relays and water pumps according to the specified thresholds, achieving a 100% system success rate. These results confirm that the system operates as expected according to the specifications.